The handbook of behavioral medicine - Mostofsky, David I. (Chichester, West Sussex : Malden, MA : Wiley-Blackwell, 2014)
Handbook of Behavioral Medicine presents a comprehensive overview of the current use of behavioral science techniques in the prevention, diagnosis, and treatment of various health related disorders. Features contributions from a variety of internationally recognized experts in behavioral medicine and related fieldsIncludes authors from education, social work, and physical therapyAddresses foundational issues in behavioral medicine in Volume 1, including concepts, theories, treatments, doctor/patient relationships, common medical problems, behavior.
Benefits of Physical Activity Participation among Overweight or Obese PeopleTypes of physical activity that lead to health benefits; Physical health benefits; Psychological health benefits; Health benefits independent of weight change; Impact of Common Comorbidities on Participation in Sport and Exercise; Physical Activity Participation Prevalence; Health Problems and Economic Burden Associated with Physical Inactivity; Detrimental Effects of Sedentary Behavior on Health; Promoting Physical Activity Participation among Obese Individuals.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Medicine and psychology -- Handbooks, manuals, etc; Health behavior -- Handbooks, manuals, etc; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Health behavior; Medicine and psychology; Health behavior -- Handbooks, manuals, etc; Medicine and psychology -- Handbooks, manuals, etc; Electronic books; Handbooks and manuals